Neem and environment / Volume 2 - Singh, R. P. (Scientist); Indian Society of Tobacco Science; World Neem Conference (1993 : Bangalore, India) (New Delhi : Oxford & IBH Pub. Co., 1996)
Proceedings of the World Neem Conference, held at Bangalore, India, from 24 to 28 February, 1993, organized by Indian Society of Tobacco Science.
Includes bibliographical references.
Keywords: Neem -- Congresses; Neem products -- Congresses